2018
DOI: 10.1590/1809-4430-eng.agric.v38n5p657-664/2018
|View full text |Cite
|
Sign up to set email alerts
|

Water Availability and Potassium Doses in Cherry Tomato Quality

Abstract: The quality of cherry tomato fruits is directly related to the management strategies used in the production system, such as irrigation and fertilization. This study aimed to assess the quality of cherry tomato fruits cultivated under water availability and potassium fertilization. The experiment was carried out in a greenhouse in pots of 12 dm 3 of an Oxisol. The experimental design was a randomized block design in a 5 2 fractional factorial arrangement with five water availabilities in the soil (4, 14, 24, 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(25 reference statements)
0
3
0
2
Order By: Relevance
“…Silva et al [17], studying fertigated crops in a substrate composed of coconut fiber, found the feasibility of using solution extractors to monitor the concentration of nutrients in the soil solution. [33] and [29] also came to the conclusion that the use of soil solution extractors is a viable alternative for ionic monitoring during the cycle of crops fertigated with high frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silva et al [17], studying fertigated crops in a substrate composed of coconut fiber, found the feasibility of using solution extractors to monitor the concentration of nutrients in the soil solution. [33] and [29] also came to the conclusion that the use of soil solution extractors is a viable alternative for ionic monitoring during the cycle of crops fertigated with high frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Intelligent systems for properly managing fertilizers and water in soil solution can be used in protected environments to minimize environmental contamination from fertigation leaching and, consequently, considerable savings of water and fertilizers are conciliated with high yields and greater water use efficiency [15,16,4,17] besides prevention and control of soil salinization in the intensively irrigated areas [3]. In these systems, the use of Time Domain Reflectometry and solution extractors associated with a mass balance equation of the applied solution [18,19] is a key tool that assists in monitoring and estimation of moisture content, controlling salinity, and nutrient application [20].…”
Section: Introductionmentioning
confidence: 99%
“…The first one refers to the increase in the electrical conductivity of the soil solution due to an increase in the concentration of KCl, a salt used as a source of potassium and characterized by having a high salt index, in addition to the presence of the chloride ion (Cl − ), which is potentially toxic to a large number of ornamental species. According toSilva et al (2018), high concentrations of some fertilizers can compromise the absorption of water and nutrients as a result of the decrease in the osmotic potential of the solution near the rhizosphere. Even though classic symptoms of the salinity effect were not observed in lisianthus plants, the reduction in LAI and, consequently, leaf surface, can be justified by the plant's attempt to reduce water loss as a strategy to adapt to the osmotic stress condition.The second possible explanation may be related to the higher potassium concentration available to the plant, which can become more efficient in photosynthetic…”
mentioning
confidence: 99%
“…Quanto ao número de pontos, o planejamento é composto por t = 1 + 2 k+1 + 2k pontos distintos, ou tratamentos, isto é, t = 13 para k = 2 fatores e t = 23 para k = 3 fatores. Na área de nutrição mineral de plantas, este planejamento vem sendo muito utilizado nas duas últimas décadas por diversos autores como Lavres Junior e Monteiro (2003), Bonfim-Silva, Monteiro e Silva (2007), Silveira e Monteiro (2010), Silveira e Monteiro (2011), Megda e Monteiro (2015), Silva et al (2018), Silva et al (2022), que realizaram diferentes ensaios para estudar a influência de diversos nutrientes, tais como o nitrogênio, potássio, cálcio e enxofre na fixação dos macronutrientes, nas características morfológicas e produtivas, como também, na qualidade da produção.…”
Section: Revisão Bibliográficaunclassified
“…Os resultados encontrados neste trabalho são similares aos encontrados por autores que analisaram a relação de nitrogênio e potássio para algumas dessas características. Para a produção de massa seca da parte aérea, segundo Bonfim- Silva et al (2018) a produção máxima do capim piatã ocorreu para doses 287 mgL −1 de nitrogênio e para a dose máxima de potássio utilizada no experimento, 360 mgL −1 . Segundo Sarmento et al (2008) a deficiência de nitrogênio prejudica o crescimento radicular do Panicum maximum e, concluíram que o aumento do sistema se dá linearmente na presença deste nutriente.…”
Section: Considerações Geraisunclassified